REVIEW OF RISK LEVEL MEASUREMENT OCCUPATIONAL HEALTH AND SAFETY IN OFFICE BPJS BONTANG CITY CONSTRUCTION ACTIVITIES - LIATI, OPE (KURVA S JURNAL MAHASISWA, 2018)
Construction activities have a wide range of risks one is the risk of occupational health and safety. Construction of  office Bpjs Bontang is a 2 floor storey construction work, requiring a lot of manpower, involving heavy equipment, so it has the potential risk to the danger of accidents. This research will be examined on   occupational   health   and   safety   risk   identification,   risk   analysis,   risk calculation, risk sequence,   risk  control, and recommendations on risk.  Data collection techniques among other observations, questionnaires, the data contractor and literature.  The method used is the description calculation of the risk level occupational health and safety   in accordance with Regulation of the Minister of Public Works 2014 on Guidelines for Occupational Health and Safety Management System Construction Sector Public Works. The final conclusion of the 13 identified risk from 38 risk construction activities, the calculation of risk level 3 variables obtained a high risk. Welding smoke inhalation variable (breathing problem) in the type of plate making activities, the electrocution worker variable on the type of ceramic installation activities and worker variable fell from a height in the type of electrical installation activities.